Outlook 2007 for dummies - Dyszel, Bill (--For dummies., 2006)
Most users take advantage of only two percent of Outlook's power; this book shows them how to harness frequently overlooked tricks and techniques that can significantly boost productivity.; Shows how to manage time and information in the new interface, covering instant searches, the To-Do bar, color categories, and task integration with OneNote, Project, Access, and Windows SharePoint Services.; Explains how to connect across boundaries with access to WSS data, two-way sync and offline access, calendar sharing, smart scheduling, RSS support, electronic business cards, and the improved out-of-o.